Electronic scanning in linear active antenna array - Pandey V.K.; Vishvakarma B.R. (My University, 2025)
The beam scanning characteristics of 1×4 linear Gunn-integrated active antenna array are investigated by varying the bias voltages of the different elements in the array keeping the side lobe level at least 10 dB down the main beam level. The optimization of beam scanning by varying the bias voltage of all the four elements simultaneously exhibited a beam scanning of 40° with power deviation of 1.85 dB in main beam, which is better than the earlier reported data.